Cochrane Database of Systematic Reviews 2007
DOI: 10.1002/14651858.cd006107.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound versus 'clinical touch' for catheter guidance during embryo transfer in women

Abstract: This review is published as a Cochrane Review in the Cochrane Database of Systematic Reviews 2016, Issue 3. Cochrane Reviews are regularly updated as new evidence emerges and in response to comments and criticisms, and the Cochrane Database of Systematic Reviews should be consulted for the most recent version of the Review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 45 publications
0
12
1
1
Order By: Relevance
“…[17] Ultrasound guidance helps in depositing embryos a-traumatically to the mid-portion of the uterus without touching the fundus. A meta-analysis of 17 Randomized controlled trials (RCT) studies conducted by Cochrane[18] comparing ultrasound vs. clinical touch showed increased pregnancy rate with ultrasound guidance. In the present study, all ETs were done under ultrasound guidance.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Ultrasound guidance helps in depositing embryos a-traumatically to the mid-portion of the uterus without touching the fundus. A meta-analysis of 17 Randomized controlled trials (RCT) studies conducted by Cochrane[18] comparing ultrasound vs. clinical touch showed increased pregnancy rate with ultrasound guidance. In the present study, all ETs were done under ultrasound guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Successful embryo transfer (ET) is arguably one of the most crucial steps of an assisted reproductive technology (ART) cycle. Several factors have been reported to affect pregnancy rates, including the ease of ET, use of ultrasound guidance, type of transfer catheters and crucially the position of embryo deposition. The latter has been the focus of several studies that have investigated both the position of the ET catheter tips and the position of the air bubbles deposited along with the embryo following ET.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews have shown that US guidance improves the clinical pregnancy, ongoing pregnancy, and live-birth rates in women when compared with the standard clinical touch method [1]- [4]. Ultrasound helps in confirming the position of the catheter tip within the uterine cavity, properly determining the site of embryo deposition, and decreasing the frequency of "difficult" ETs [2].…”
Section: Introductionmentioning
confidence: 99%